Comparative study about social support network among familiar physicians and traffic officers, México - Aranda B., Carolina (2010)
The social support is the process that occurs between people that make up the social network of a subject. Actions such as listening, estimate, assess, and so on, are behaviors that occur among individuals who make up the network. The aim of this study analyze the situation of social support and social support networks on family physicians and traffic agents of a city in Mexico. 197 physicians and 875 traffic agents participated voluntarily with an informed consent. The information was collected through a questionnaire with soci.demographic and labor ítems in addition to the amended Social Resources Inventory of Veiga Diaz; which was analyzed descriptively and inferentially. Among the most important results we found that most of the population has adequate social support network and that the only significant associations were between the objective and subjective family network with the friends; and, between the sons/daughters with the familiar and labor subjective networks. The support networks play an important role as protective factors against any critical situation with the aim of contributing to a better quality of life.